Potential of Cassava Peel as Cr Metal Biosorbent in Laboratory COD Waste - Farhan Fatur Rachman; Yulian Syahputri; Sutanto Sutanto (Helium: Journal of Science and Applied Chemistry, 2023)
Cassava peel is an agricultural residual waste that can be found from industrial processing in Indonesia. Cassava peel contains cellulose which can be used as a biosorbent. The aim of this study was to optimize the adsorption of cassava peel waste on chromium metal ions and then to determine the adsorption capacity and adsorption constant values of the Langmuir model and the Freundlich model. The research was divided into four stages, namely manufacture, optimization conditions, maximum capacity, and application to waste. Optimization conditions for weight ratio, optimum concentration, pH, and contact time. Determination of chromium content, standard series, and testing using the APHA method SSA ed. 23rd 3030 D 3111 B, 2017 at a wavelength of 357.78 nm. Determination of adsorption isotherms of Langmuir and Freundlich models. The optimum condition results at a weight ratio of 1 gram in 10 ml of solution, a concentration of 10 ppm, pH 2, and a contact time of 180 minutes. The adsorption capacity is 0.10216 mg Cr/gram cassava peel biosorbent. Application to chrome contamination laboratory waste obtained an adsorbed concentration of 20.681 ppm. In the Langmuir and Freundlich isothermal model, the R2 value is 0.9668 and 0.9985, the n value is 0.73964.